PENGARUH MODEL PEMBELAJARAN KOOPERATIF TIPE TWO STAY TWO STRAY (TSTS) TERHADAP HASIL BELAJAR IPA - Fida Ristiana; Yuli Prihatni (TRIHAYU: Jurnal Pendidikan Ke-SD-an, 2016)
The purpose of research Influence of Cooperative Learning Model Type Two Stay Two Stray (TSTS) of the IPA Learning Result Highlights Natural Resources Grade IV SD N Kotagede 3 in academic year 2015/2016. This research was experimental. Population and sample in this study were all students of class IV consists of two classes totaling 58 students. Collecting data using documentation technique and test technique. Data analysis techniques using by using t-test after test requirements, test distribution normality and homogeneity of variance. The resultthere of research indicate is a significant difference of learning result IPA subject of natural resources students fourth grade SD N Kotagede 3 in academic year 2015/2016 between the taught using cooperative models with the two stay two stray (TSTS) laearning taught using conventional models. This means it can be concluded there is the influence of the use of models laearning two stay two stray (TSTS) cooperative to learn science result of students.